Rancang Bangun Aplikasi E-Payment Menggunakan Famework Togaf Adm Studi Kasus PT XYZ - Lufty Abdillah (KALBISCIENTIA Jurnal Sains dan Teknologi, 2022)
PT XYZ is a subsidiary established by IPC, specifically dealing with logistics services. In its business process, PT XYZ provides services to customers for more than one transaction regardless of whether the transaction has been completed or not. A condition that often occurs is when a customer makes a payment (via bank transfer), customer rarely attaches information about the payment that has been made. Customers also usually make payments for more than one note in one transfer. This poses a problem because PT XYZ has difficulty identifying payments made by customers. The purpose of this study is to analyze and design an E-Payment Application. This is done so that customers can receive bills and make payments that have been integrated with PT XYZ's financial application, thereby minimizing the risk of payment errors. The method of analysis and design of this E-Payment application will use THE OPEN GROUP ARCHITECTURE FRAMEWORK (TOGAF) by utilizing Cloud Computing technology. The final result of this research is the design of an e-payment application in the form of a TOGAF framework that can be used by PT XYZ to develop and implement an e-payment system in the company.